Mitochondrial genome of Rattus tiomanicus (Rodentia: Muridae) and molecular phylogeny of murinae - Song, Sze-Looi; Lim, Phaik-Eem; Yong, Hoi-Sen; Tan, Ji (Penerbit Universiti Kebangsaan Malaysia, 2021)
Rattus tiomanicus is a murid rodent of considerable agricultural and public health importance in Southeast Asia. The whole mitochondrial genome of R. tiomanicus was sequenced by the Ion Torrent PGM platform. It had a total length of 16,309 bp, consisting of 13 protein-coding genes, two rRNA genes, 22 tRNA genes and two non-coding regions (L-strand replication origin and control region). Only TAA and incomplete T-stop codons were represented in the protein-coding genes. Of the tRNAs, tryptophan (W) had ACU anticodon. The cloverleaf structure for serine S1 (AGN) tRNA lacked the entire D-arm, while in lysine (K) tRNA, the DHU arm lacked the D-loop. Molecular phylogeny based on 15 mt-genes indicated R. tiomanicus having closest genetic affinity to R. rattus complex (R. rattus, R. tanezumi). There were two major clades for the Murinae subfamily namely the Rattini tribe and the Apodemini, Murini and Hydromyini tribes. The whole mitogenome of R. tiomanicus will serve as a useful dataset for studying the systematics and phylogenetic relationships of the murid rodents.